Stock Selection Strategies in Emerging Markets - Jaap van der Hart; Erica Slagter; Dick van Dijk (Tinbergen Institute, 2001)
Recent empirical evidence suggests that value and momentum strategies generate significantexcess returns in emerging markets. We confirm these results and extend them in severaldirections. First, we examine a broader range of stock selection strategies, including strategiesbased on analysts' earnings revisions. We also consider multivariate strategies, whereby stocks areselected on multiple characteristics, and find that this enhances the overall performance. Excessreturns also increase if country selection is incorporated into the strategies, but the risk of thestrategies increases proportionally. Second, we test whether the strategies can be implementedsuccessfully in practice by a large institutional investor, facing a lack of liquidity, restrictions onforeign ownership and substantial transaction costs. We find that even under such more realisticcircumstances the strategies earn significant excess returns. Third, we examine several popularexplanations for the excess returns. We find no evidence of higher market risk or lower liquidity ofthe strategies. Instead, based on the developments of earnings and earnings revisions afterportfolio formation, we find that the results are consistent with behavioral explanations.
Keywords: G11; G15; 330; value; momentum; earnings revisions; market imperfections; risk; behavioral models; overreaction; underreaction; Portfolio-Management; Kapitalanlage; Schwellenländer; Theorie